Galectin‐3 and ST2 as predictors of therapeutic success in high‐risk patients undergoing percutaneous mitral valve repair (MitraClip). Issue 9 (20th August 2018) - Dörr, Oliver; Walther, Claudia; Liebetrau, Christoph; Keller, Till; Sommer, Thomas; Boeder, Niklas; Bayer, Matthias; Bauer, Pascal; Möllmann, Helge; Gaede, Luise; Troidl, Christian; Voss, Sandra; et al.
Abstract : Background: Percutaneous mitral valve repair (PMVR) is an interventional treatment option in patients with severe mitral regurgitation (MR) and at high risk for open‐heart surgery. Currently, limited information exists about predictors of procedural success after PMVR. Galectin‐3 (Gal‐3) and suppression of tumorigenicity 2 (ST2) induce fibrotic alterations in severe MR and heart failure. We sought to examine the predictive value of Gal‐3 and ST2 as specific indicators of therapeutic success in high‐risk patients undergoing PMVR. Hypothesis: We hypothesize that extended cardiac fibrotic alterations might have impact on successful MR reduction after the MitraClip procedure. Methods: A total of 210 consecutive patients undergoing PMVR using the MitraClip system were included in this study. Procedural success was defined as an immediate reduction of MR by ≥2 grades, assessed by echocardiography. Venous blood samples were collected prior to PMVR and at 6 months follow‐up for biomarker analysis. Results: After PMVR there was a significant reduction in the severity of MR (MR grade: 3 ±0.3 vs 1.6 ±0.6, P <0.001). Low baseline Gal‐3 levels (PMVRsuccess : 22.0 ng/mL [IQR, 17.3‐30.9] vs PMVRfailure : 30.6 ng/mL [IQR, 24.8‐42.3], P <0.001) and ST2 levels (PMVRsuccess : 900.0 pg/mL [IQR, 619.5‐1114.5] vs PMVRfailure : 1728.0 pg/mL [IQR, 1051.March 1, 1930], P < 0.001) were associated with successful MR reduction after PMVR. Also, ROC analysis identified low baseline Gal‐3 and ST2 levels as predictors of therapeutic success after PMVR (AUCGal‐3 :0.721 [IQR, 0.64‐0.803], P < 0.001; AUCST2 : 0.807 [IQR, 0.741‐0.872], P < 0.001). Conclusions: There was an association between low Gal‐3 and ST2 plasma levels and successful MR reduction in patients with severe MR undergoing PMVR using the MitraClip system.